Pathogenesis of Enamel-Renal Syndrome Associated Gingival Fibromatosis: A Proteomic Approach - Simancas Escorcia, Victor; Guillou, Clément; Abbad, Lilia; Derrien, Louise; Rodrigues Rezende Costa, Claudio; Cannaya, Vidjea; Benassarou, Mourad; Chatziantoniou, Christos; Berdal, Ariane; Acevedo, Ana Carolina; Cases, Olivier; Cosette, Pascal; et al. (Frontiers in Endocrinology, 2021)
The enamel renal syndrome (ERS) is a rare disorder featured by amelogenesis imperfecta, gingival fibromatosis and nephrocalcinosis. ERS is caused by bi-allelic mutations in the secretory pathway pseudokinase FAM20A. How mutations in FAM20A may modify the gingival connective tissue homeostasis and cause fibromatosis is currently unknown. We here analyzed conditioned media of gingival fibroblasts (GFs) obtained from four unrelated ERS patients carrying distinct mutations and control subjects. Secretomic analysis identified 109 dysregulated proteins whose abundance had increased (69 proteins) or decreased (40 proteins) at least 1.5-fold compared to control GFs. Proteins over-represented were mainly involved in extracellular matrix organization, collagen fibril assembly, and biomineralization whereas those under-represented were extracellular matrix-associated proteins. More specifically, transforming growth factor-beta 2, a member of the TGFβ family involved in both mineralization and fibrosis was strongly increased in samples from GFs of ERS patients and so were various known targets of the TGFβ signaling pathway including Collagens, Matrix metallopeptidase 2 and Fibronectin. For the over-expressed proteins quantitative RT-PCR analysis showed increased transcript levels, suggesting increased synthesis and this was further confirmed at the tissue level. Additional immunohistochemical and western blot analyses showed activation and nuclear localization of the classical TGFβ effector phospho-Smad3 in both ERS gingival tissue and ERS GFs. Exposure of the mutant cells to TGFB1 further upregulated the expression of TGFβ targets suggesting that this pathway could be a central player in the pathogenesis of the ERS gingival fibromatosis. In conclusion our data strongly suggest that TGFβ -induced modifications of the extracellular matrix contribute to the pathogenesis of ERS. To our knowledge this is the first proteomic-based analysis of FAM20A-associated modifications.